Efeito da temperatura na anestesia com mentol em Guppy (Poecilia reticulata) - Lamberti, Luana Gabrieli (2019)
Plant essential oils for fish anesthesia are an alternative to the use of expensive chemicals, which could be expensive and cause damage to animals. However, although they have numerous advantages in reducing stress, anesthetic efficacy may be influenced by factors such as animal size, age, sex and species; in addition to environmental factors such as water temperature. Therefore, the objective of present study was to evaluate different menthol concentrations for Guppy (Poecilia reticulata) anesthesia and water temperature influence during the procedure. Two experiments were performed: first, animals were divided into females, males and juveniles and individually submitted to menthol concentrations of 50, 100, 150 and 200 mg L-1 , and second, animals were anesthetized with menthol 100 mg L-1 at 24, 27 and 30oC. The induction and recovery times, verified through physiological and behavioral changes, were timed, as well as survival after the experiment was evaluated. Analysis of variance and comparison of means were performed by two-way ANOVA, followed by Tukey's test (5%). Results indicate that menthol can be used as an anesthetic for Guppy in higher concentrations, because 50 mg L-1 dose was not enough for animals to reach deep anesthesia stage. Doses between 100 and 200 mg L-1 were efficient for anesthesia in the three categories, in a dose dependent manner. Regarding the temperature, it was possible to verify a direct influence on induction and recovery times, in which 30oC temperature presented the shortest times during anesthetic procedure, as expected for a pecilothermal animal. It was also possible to observe greater sensitivity of juveniles during anesthesia compared to adults. Finally, considering the lowest dose required for anesthetic induction, a concentration of 150 mg L-1 is recommended for Guppy females, males and juveniles.